Gandjariella thermophila gen. nov., sp. nov., a new member of the family Pseudonocardiaceae, isolated from forest soil in a geothermal area. Issue 10 (22nd July 2019) - Ningsih, Fitria; Yokota, Akira; Sakai, Yasuteru; Nanatani, Kei; Yabe, Shuhei; Oetari, Ariyanti; Sjamsuridzal, Wellyzar
Abstract : Six mycelium-forming actinomycete strains were isolated from forest soil near the Cisolok geysers in West Java, Indonesia. The 16S rRNA gene sequences of these strains showed high similarity to members of genera in the family Pseudonocardiaceae with values less than 96.0 %, and most closely related to the genus Thermotunica, T. guangxiensis AG2-7 T (94.6–95.2 % similarity). The type strain, designated SL3-2-4 T, was aerobic, thermophilic, Gram-stain-positive that formed branched, non-fragmented substrate mycelia and unbranched aerial mycelia with long-chain, oval-shaped spores on International Streptomyces Project (ISP) 3 medium. It produced light-orange substrate mycelia and light-orange diffusible pigments on ISP 3 medium with 2 % gellan gum, grown at 30–55 °C, with optimum growth at 45 °C. The pH range for growth was 4.0–8.0, with optimum growth at pH 7.0. Strain SL3-2-4 T was able to hydrolyze casein, esculin, gelatin, guanine, hypoxanthine, starch, L-tyrosine, and xanthine, but not adenine, carboxymethyl-cellulose, cellulose, chitin, Tween 20, or xylan. The major fatty acid was iso -C16 : 0, and the major menaquinone was MK-8 (H4 ). The detected polar lipids were diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, phosphatidyl- N -methylethanolamine, unidentified aminophospholipids, unidentified glycolipids, and unidentified phospholipids. The cell wall hydrolysate of SL3-2-4 T contained meso -2, 4-diaminopimelic acid. The whole cell sugars were arabinose and galactose. The DNA G+C content was 71.6 mol%. Phenotypic features and phylogenetic data differentiated SL3-2-4 T from members of the family Pseudonocardiaceae . Therefore, the strain SL3-2-4 T is proposed as a representative of a novel species in a novel genus, Gandjariella thermophila gen. nov., sp. nov. The type strain is SL3-2-4 T (=UICC B-83 T =NRRL B-67478 T =InaCC A981 T ).